Utilization of rehabilitation services for BPJS stroke outpatients in indonesia - Sutejo, Mianti Nurrizky; Hafidz, Firdaus; Pinzon, Rizaldy (BKM Public Health and Community Medicine, 2021)
Purpose: JKN has been implemented since 2014; however, there has been no change in the value of access to and utilization of medical rehabilitation services, particularly physiotherapy, in FKRTLs in Indonesia. This research aims to identify the factors that influence the pattern of outpatient physiotherapy services received by stroke patients at BPJS Kesehatan during the treatment period. Methods: This study employs an analytical approach using secondary data from the 2015-2016 BPJS Health Data Sample, with a cross-sectional study design. The data were analyzed using univariable and bivariable analyses with the chi-square test, as well as multivariable analysis with logistic regression, with an α level of 0.05. Results: The analysis of patients with stroke cases yielded only 1,641 participants who visited physiotherapy services, and 3 participants from stroke cases who visited rehabilitation services, out of the total participants of BPJS Health in 2015-2016. Frequency of visits to health services for stroke cases among BPJS Kesehatan participants, based on gender, age, province of residence of the participant, type of participation, type of stroke, stroke comorbidity, type of hospital, and cost of claims. Conclusion: This study showed that only a very small number of stroke patients attend rehabilitation services. The utilization services are related to sex, living area, type of stroke, and comorbidities.